Inter-firm efficiency comparisons: U.S. and U.K. manufacturing enterprises in Britain - J.H. DUNNING; D. ROWAN (PSL Quarterly Review, 2014)
The paper suggests a method of evaluating the efficiency of firms with a view to comparing the performance of British and U.S. firms operating in the United Kingdom. The authors first give a brief preliminary account of the origins and aims of the study for which a means of undertaking inter-firm efficiency comparisons is required. They go on to define the efficiency of the firm and propose an operational measure of efficiency as defined. A number of tests of the proposed measure are then carried out, and certain tentative conclusions regarding the relative efficiency of British and U.S. firms in the United Kingdom are drawn.